DEVELOPMENT OF FEMALE STUDENTS’ PHYSICAL QUALITIES THROUGH AEROBICS - Yakhshiyeva Mekhrinigor Shavkatovna (International Journal of Literature and Language Studies, 2026)
The development of physical qualities among female students is an important aspect of modern physical education in higher education institutions. Aerobics, as a structured form of rhythmic physical exercise, has gained significant attention due to its accessibility, motivational character, and comprehensive impact on the human body. This study investigates the effectiveness of aerobics training in improving key physical qualities, including endurance, strength, flexibility, coordination, agility, and overall physical fitness among female students